2019
DOI: 10.1007/s40097-019-0294-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of graphene oxide-supported meso-tetrakis (4-carboxyphenyl) porphyrinatoiron (III) chloride as a heterogeneous nanocatalyst for the mercaptan removal from the gas stream

Abstract: Sulfur compounds are one of the major problems and undesirable contaminants in the oil and gas industries. To address this issue, mercaptan removal from the gas stream in a fixed bed reactor under nanocatalyst was investigated. In this work, meso-tetrakis (4-carboxyphenyl) porphyrinatoiron (III) chloride-supported graphene oxide [GO-FeTCPP (Cl)] nanocatalyst was synthesized and adsorption of mercaptan on nanocatalyst was studied. Fourier-transform infrared spectroscopy (FT-IR), scanning electron microscopy (SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Alginate adsorbents have restricted use because of their low mechanical strength and durability. Combining alginates with other materials such as graphene oxide (Mirzaeian et al 2019 ; Malinga and Jarvis 2020 ), activated carbon or graphite with suitable particle size distribution and large pores, high adsorption capacity, and specific surface area (Ahmadi et al 2021 ) has improved their mechanical qualities (Rajabiet al 2017 ). Rajendran et al ( 2021 ) reported that carbon-based materials and their composites are super capacitors due to their high efficiency, superior energy densities, low cost, and prolonged life span (Rajendran et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Alginate adsorbents have restricted use because of their low mechanical strength and durability. Combining alginates with other materials such as graphene oxide (Mirzaeian et al 2019 ; Malinga and Jarvis 2020 ), activated carbon or graphite with suitable particle size distribution and large pores, high adsorption capacity, and specific surface area (Ahmadi et al 2021 ) has improved their mechanical qualities (Rajabiet al 2017 ). Rajendran et al ( 2021 ) reported that carbon-based materials and their composites are super capacitors due to their high efficiency, superior energy densities, low cost, and prolonged life span (Rajendran et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…2C and D). 63–65 For instance, Zare-Dorabei et al showcased the attachment of TPPH to GO via an esterification process. This TPPH–GO hybrid was then examined for its utility as an optical sensor in detecting mercury ions.…”
Section: Synthesis Routes For the Functionalization Of Gbms With Porp...mentioning
confidence: 99%
“…63 In a separate study, Mirzaeian et al achieved the functionalization of GO using the Fe( iii ) complex TCPP via an ester linkage. 65 The resulting material was investigated for its effectiveness as a catalyst in the removal of mercaptan from gas streams.…”
Section: Synthesis Routes For the Functionalization Of Gbms With Porp...mentioning
confidence: 99%
“…For example, Mirzaeian et al functionalized GO with the Fe(III) complex of 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) and studied its performance as a catalyst for the mercaptan removal from a gas stream. 143 In another study, Santos et al reported the functionalization of GO directly to porphyrins previously functionalized with different glycol branches. [144] In this case, there was a primary step of carboxylation of GO using chloroacetic acid in basic conditions to maximize the number of À CO 2 H groups, which were then covalently linked (by ester bonds) to the glycol branches of the functionalized porphyrin (Scheme 8).…”
Section: Tgamentioning
confidence: 99%